Information System for Monitoring the Progress of Clean Water Pipeline Installation Projects Using A Web-Based Dashboard and the Prototype Model Method at PT Bestindo Putra Mandiri - Martinus Gawi Tiga; Nur Azizah; Haryanto Haryanto; Raka Wicaksono (Technema: Journal of Intelligent Engineering and Computing, 2026)
Project progress monitoring at PT Bestindo Putra Mandiri previously relied on Microsoft Excel, photographic documentation, and report submission through communication media, resulting in fragmented data management, delayed information retrieval, and inefficient progress recapitulation. This study aimed to develop a web-based information system for monitoring the progress of clean water pipeline installation projects using a dashboard and the Prototype Model at PT Bestindo Putra Mandiri. The study employed an empirical system-development design involving direct user interaction and functional evaluation of the developed application. System requirements were identified through observation and user interaction, followed by iterative development consisting of requirement identification, prototype design, prototype development, user evaluation, refinement, and implementation of the finalized system. The developed system integrates project data, work progress, project locations, field documentation, verification status, targets, realization, and reporting into a centralized web-based environment. The dashboard presents project completion percentages, progress status, target and realization information, and graphical representations to support monitoring by SPV Trunk Main/SPV Infill, Construction Manager, and Project Manager. Functional evaluation was conducted using Black Box Testing by examining authentication, project management, progress recording, documentation, verification, dashboard visualization, status information, and reporting functions. The testing results showed that the tested functions generated outputs consistent with their expected behavior. The system provides an integrated monitoring environment that improves information accessibility and supports structured project progress monitoring and managerial evaluation.